Perbandingan Pendidikan Islam di Asia Tenggara - susanto, Pendi; Pendi Susanto (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Islamic education in Southeast Asia has some diverse substances. In Indonesia, Islamic education experience rapid progress. Indonesia employs Islamic education as a compulsory subject in schools and public universities. In Malaysia, Islamic education has many improvements since 1956 e.g. Islamic education is taught in national school, and also Malaysia also formed a religious education department that handles every religious subject in schools. Thailand, especially in a couple of regions such as Pattani, Setul, Yala, and Narathiwat, Islamic education with boarding school, and Madrasah become Islamic identity backbone and Islamic struggle against the central government. Meanwhile, the different condition takes place to Islamic education in Singapore. There is still an unclear purpose between Islamic education with the national education system, there is no Islamic university, no standard curriculum, no central Islamic education administration, and the lack of fund and economical status of religion teacher.